2017
DOI: 10.1186/s12909-017-0904-5
|View full text |Cite
|
Sign up to set email alerts
|

Influence of feedback characteristics on perceived learning value of feedback in clerkships: does culture matter?

Abstract: BackgroundVarious feedback characteristics have been suggested to positively influence student learning. It is not clear how these feedback characteristics contribute to students’ perceived learning value of feedback in cultures classified low on the cultural dimension of individualism and high on power distance. This study was conducted to validate the influence of five feedback characteristics on students’ perceived learning value of feedback in an Indonesian clerkship context.MethodsWe asked clerks in Neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 31 publications
5
27
0
Order By: Relevance
“…This could reflect cultural norms regarding roles in learning, in which teachers are leaders, guides and masters [27]. This finding also resonates with recent research in East Asian countries that support the educational value of the mini-CEX [15,16]. Traditional teacher-centred Chinese and medical cultures highlight a power differential [15,27,29,46].…”
Section: Making Sense Of Assessment Through Interactionsupporting
confidence: 80%
See 1 more Smart Citation
“…This could reflect cultural norms regarding roles in learning, in which teachers are leaders, guides and masters [27]. This finding also resonates with recent research in East Asian countries that support the educational value of the mini-CEX [15,16]. Traditional teacher-centred Chinese and medical cultures highlight a power differential [15,27,29,46].…”
Section: Making Sense Of Assessment Through Interactionsupporting
confidence: 80%
“…Furthermore, the acceptability of educational innovation may determine the utility of the mini-CEX in new cultural contexts [14,15]. Studies in southeast Asia have indicated variability in shared understanding and acceptance of the mini-CEX [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…In this regards, positive role-modeling process in showing empathy from the superior level can become a strength point for medical students’ empathy development. Studies on the influence of hierarchical culture on feedback [34] and clinical reasoning teaching and learning [35] show that acknowledgement of culture in a certain setting is critical to facilitate development process of medical students’ competencies.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, cultural differences also in uence the perceived learning value of feedback. Indonesian medical students recognized characteristics of four valuable feedback consisting of weaknesses mentioned by provider, comparing performance to a standard, explaining or demonstrating the correct performance, and preparing an action plan with the student [14]. Appraisal of good performance, another valuable characteristic of feedback, was not valued from Indonesian students.…”
Section: Introductionmentioning
confidence: 99%